Measurements of branching fractions and CP asymmetries and studies of angular distributions for B →[phi][phi]K decays - Lees, Jean-Pierre; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We present branching fraction and CP asymmetry measurements as well as angular studies of B→ϕϕK decays using 464×106 B¯¯¯B events collected by the BABAR experiment. The branching fractions are measured in the ϕϕ invariant mass range below the ηc resonance (mϕϕ<2.85 GeV). We find B(B+→ϕϕK+)=(5.6±0.5±0.3)×10−6 and B(B0→ϕϕK0)=(4.5±0.8±0.3)×10−6, where the first uncertainty is statistical and the second systematic. The measured direct CP asymmetries for the B± decays are ACP=−0.10±0.08±0.02 below the ηc threshold (mϕϕ<2.85 GeV) and ACP=0.09±0.10±0.02 in the ηc resonance region (mϕϕ in [2.94, 3.02] GeV). Angular distributions are consistent with JP=0− in the ηc resonance region and favor JP=0+ below the ηc resonance.